Body mass index and pharmacodynamics of target‐controlled infusion of propofol: A prospective non‐randomized controlled study. (11th January 2022) - Wu, Zijuan; Gong, Jinhong; He, Xiaomei; Wu, Zhouquan; Shen, Jingjing; Shang, Jingjing
Abstract: What is known and objective: In our preliminary study, there were large individual variations at sedation levels during propofol target‐controlled infusion (TCI). The present study aimed to assess the effects of body mass index (BMI) on the pharmacodynamic index of propofol TCI. Methods: This prospective, non‐randomized controlled trial evaluated 175 female patients undergoing breast lumpectomy. Anesthesia was induced with propofol using the TCI system embedded Schnider model. The effect compartment concentration was set to 3 μg/ml, and the start time of infusion was recorded. When the target concentration reached 3 μg/ml, the patient could not be awakened (Ramsay sedation score ≥4), and when the Bispectral Index (BIS) was <60, the infusion was discontinued, and the time point was recorded. The observation end‐point was set at the Observer's Assessment of Alertness/Sedation (OAA/S) score of <4. The correlation between the BMI and the pharmacodynamic index of propofol was evaluated. Results and discussion: Propofol induction time was significantly correlated with the BMI ( p  < 0.001). The induction time of the underweight subjects was 10.14 ± 2.19 min, which was remarkably higher than that of normal weight (6.48 ± 3.44 min) and overweight (4.75 ± 2.53 min) individuals ( p  < 0.001). There were still significant differences after multivariable‐adjusted regressions ( p  < 0.001). There were no significant differences in recovery time and sedative effect indicators, such as Ramsay score, BIS value, and effect compartment concentration, between the three groups ( p  > 0.05 for all). What is new and conclusion: These results suggest that the BMI is one of the critical factors affecting the pharmacodynamic index of propofol TCI, and the induction time decreased progressively with increasing BMI. The Schnider model might underpredict doses of propofol for underweight individuals. Abstract : BMI is one of the critical factors affecting the pharmacodynamic index of propofol target‐controlled infusion, and the induction time decreased progressively with increasing BMI. The Schnider model might underpredict doses of propofol for underweight individuals.